Education Financing Planning Strategy in the Field of Middle School Education Development, Maybrat Regency Education Office - Air, Bonifasius; Sumual, Shelty D. M. (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to examine education financing planning strategies in the field of junior high school education development at the Maybrat District Education Office. This study was carried out using a bibliographic approach, which involved collecting secondary data from various relevant literature sources. The main findings of this research show that the main source of education financing in Maybrat Regency comes from the Regional Revenue and Expenditure Budget (APBD) and School Operational Assistance Funds (BOS). However, this funding allocation is often insufficient to meet school operational and development needs. In addition, some schools are trying to find alternative funding sources through collaboration with private institutions and non-governmental organizations, although these initiatives are still limited. This research also found that transparency and accountability in the management of education funds need to be improved through financial management training and the implementation of an integrated financial information system. In addition, annual budget planning carried out by schools in Maybrat Regency needs to be performance-based and more flexible in dealing with changing needs. Other challenges include limited facilities and infrastructure, as well as limited accessibility due to remote geographical conditions. Recommendations from this research include diversifying funding sources through developing partnerships with the private sector and non-governmental organizations, strengthening financial management capacity through regular training, optimizing the use of funds through performance-based budgeting, and increasing community involvement in planning and monitoring education financing. It is hoped that the implementation of these strategies can improve the quality of education and create a more conducive learning environment for students in Maybrat Regency.